SURGICAL SITE INFECTION AND PATTERN OF ANTIBIOTIC USE IN A TERTIARY CARE HOSPITAL IN PESHAWAR - Jan, Waqar Alam; Khan, Sajjad Muhammad; Jehanzeb, Muhammad; Muazzam, Muazzam (Journal of Ayub Medical College Abbottabad, 2010)
Background: Surgical site infection (SSI) is most common complication following surgical procedures. The objective of the study was to collect information on SSI regarding the most frequent pathogen in cases operated in casualty of Lady Reading Hospital (LRH) Peshawar, and sensitivity of the isolated pathogens to different antibiotics used. Methods: The study was carried out at surgical ’˜B’ unit (SBU) LRH from Jan 1, 2009 till Dec 31, 2009. A total of 100 patients who developed SSI after being operated for peritonitis following traumatic gut perforations, perforated appendix and enteric perforation. The patients included presented to casualty, operated in casualty OT and were shifted to the SBU, LRH. Children and patients operated on the elective list were excluded. Data was collected on specially designed proforma. Demographic details, details of SSI, culture/sensitivity reports and antibiotic used for prophylaxis and after C/S report were recorded. Results: Out of a total of 100, 72 had superficial, 20 had organ/space and 8 had deep SSI. Organisms were isolated in 77 cases (77%). E. coli being most common pathogen (46%), followed by Pseudomonas (23%), mixed growth of Staph. Aureus or MRSA (13%), MRSA (5%) AND Staph aureus (4%) in descending order. No growth was reported in 23% of cases. Conclusion: E.coli was the most common organism involved in SSI in SBU LRH. The incidence of infection with MRSA in our unit is high. Combination of antibiotics like pipreacillin/Tazobactam, Cefoperazone/Sulbactam, were most effective against the isolated organisms, except MRSA where Linezolid , vancomycin and Tiecoplanin were effective. Keywords: Surgical site infection (SSI), antibiotics, drug resistance